Rail networks are future of Malaysian logistics - Marco, Tieman (The New Straits Times Press (M) Bhd., 2017)
WITH the completion of the Mass Rapid Transit (MRT) rail line last month, Malaysia is another excellent rail infrastructure richer. My personal experience in using the MRT for business meetings in KL Sentral and dinners in Bukit Bintang has been positive.